Pengaruh Aplikasi Larutan Hara A dan B Ke Daun Dan Macam Teknologi Pemupukan Terhadap Pertumbuhan Dan Hasil Tanaman Cabai Merah Besar (Capsicum annum L.) Varietas Baja F1 - Turmuktini, Tien; Nurul Hakim, Anisa; Surya Mulya, Agus; Natalie Fitriatin, Betty; Simarmata, Tualar (OrchidAgro, 2024)
This research was conducted from May to September 2022 in the experimental field of the Faculty of Agriculture, Padjadjaran University, Jatinangor District, Sumedang Regency, at an altitude of 700 meters above sea level. This study aims to study the interaction between the application of nutrient solution to the leaves and the type of fertilizer on the growth and yield of large red chili (Capsicum annum L.) Baja F1 variety. The Environmental Design used a Split plot design consisting of two treatments which were repeated 4 times. The main plot was application of nutrient solution to leaves (F) which consisted of two levels: f0 (without application) and f1 (application of nutrient solution to leaves every 10 days). Subplots were the fertilization technology (M) which consisted of four levels: m0 (nutrient solution), m1 (4 tons ha-1 cow compost), m2 (6 kg ha-1 bioamelioran) and m3 (4 tons ha-1 amelioran plus) ). The experimental results showed an interaction between the application of nutrient solution to leaves and the type of fertilizer on growth (plant height 1, 2, 3, 4, 5 WAP, number of leaves 1, 2, 3, 4, 5 WAP, stem diameter 1, 2, 3, 4, 5 WAP) and yield (number of fruits per plant and weight per fruit) of chili plants. Application of nutrient solution to leaves and bioamelioran showed the best results on growth (plant height at 2, 3, 4, and 5 WAP, number of leaves at 1, 2, 3 and 4 WAP, stem diameter 4 and 5 WAP) and yield of chili plants ( number of fruits per plant). The type of amelioran plus fertilizer without the application of nutrient solution to the leaves gave the best results on the growth of chili plants (plant height at 1 WAP, number of leaves at 5 WAP, and stem diameters of 1, 2, and 3 WAP). Types of bioamelioran fertilizers without the application of nutrient solution to the leaves give the best results on chili plant yield (weight per fruit). Keywords: Amelioran plus, Application of nutrient solution to leaves, Bioamelioran, Cow compost,  Nutrient solution A and B, red chili.